Ammonoids of the Middle Devonian family Maenioceratidae in the Anti-Atlas of Morocco - Bockwinkel, Jürgen; Korn, Dieter (European Journal of Taxonomy, 2024)
The ammonoids of the family Maenioceratidae from Givetian sedimentary rocks of the Anti-Atlas (Morocco) are investigated. The study is based on new collections stored in the Museum für Naturkunde, Berlin. The genera Maenioceras Schindewolf, 1933 and Afromaenioceras Göddertz, 1987 are revised; the genus Trimaenioceras is newly described. The species Maenioceras afroterebratum sp. nov., Maenioceras mzerrebense sp. nov., Maenioceras oufranense sp. nov., Maenioceras beckeri sp. nov., Afromaenioceras sulcatostriatum (Bensaïd, 1974), Afromaenioceras hiemale sp. nov., Afromaenioceras bensaidi sp. nov., Afromaenioceras brumale sp. nov., Afromaenioceras crassum (Bensaïd, 1974), Trimaenioceras klugi gen. et sp. nov., Trimaenioceras eculeus gen. et sp. nov., Trimaenioceras fuscina gen. et sp. nov. and Trimaenioceras paucum gen. et sp. nov. are described in detail.